RETRACTED: Semantic Structures of Vietnamese Perception Verbs: A Cognitive and Cultural Analysis - Ly Ngoc, Toan (Jurnal Arbitrer, 2024)
This article has been retracted at the request of the author. After publication, the author notified the editorial office of significant issues related to incorrect and inappropriate citation of sources as well as inaccurate reference entries that could potentially mislead readers and compromise the academic integrity of the work. The errors were not detected during the peer-review process and were brought to light post-publication. The author takes full responsibility for the oversight and has requested the retraction in accordance with their commitment to ethical scholarly practice. The editorial board of Jurnal Arbitrer supports this decision and has retracted the article in line with the guidelines provided by the Committee on Publication Ethics (COPE). For details on our retraction policy, please visit:https://arbitrer.fib.unand.ac.id/index.php/arbitrer/correction